Testotoxicosis without Testicular Mass: Revealed by Peripheral Precocious Puberty and Confirmed by Somatic LHCGR Gene Mutation. (2nd January 2020) - Daussac, A.; Barat, P.; Servant, N.; Yacoub, M.; Missonier, S.; Lavran, F; Gaspari, L.; Sultan, C.; Paris, F.
ABSTRACT: Purpose : Testotoxicosis is an autosomal dominant form of limited gonadotropin-independent precocious puberty in boys. It is caused by a heterozygous constitutively activating mutation of the LHCGR gene encoding the luteinizing/hormone receptor (LHR). Some twenty mutations of the LHCGR gene have been reported. Most of them are constitutive mutations isolated from blood leukocyte DNA, although others are somatic, found only in testicular tumoural tissue. In all the previously reported cases of these somatic mutations, the tumour, whether a nodular Leydig cell adenoma or hyperplasia, was easily visible on testicular ultrasonography. The aim of this study was to describe an unusual presentation of a patient with the clinical and hormonal characteristics of testotoxicosis but no well-circumscribed lesion at testicular ultrasonography. Materials and Methods : Molecular analysis of the LHCGR gene was performed by direct sequencing of DNA extracted from peripheral leucocytes and testicular biopsy. Results : Molecular analysis didn't find any LHR mutation in blood, whereas it revealed for the first time a somatic D578H mutation in testicular tissue despite no evidence of a nodular aspect at testis ultrasonography. Conclusions : This observation underlines the need to look for a somatic LHCGR gene mutation from the testicular biopsies of all boys with testotoxicosis with no constitutive LHCGR gene mutation identified from blood DNA, even in the absence of circumscribed testicular lesion at ultrasonography. In addition, based on the known link between LHR mutations and testicular tumourigenesis, yearly ultrasound monitoring of the testes should be considered for these patients.